Perception of English Language Studies Students on the use of Open Educational Resources (OER) for Remote Learning - Labicane, Gianinna Elaine; Oliva, Ricky Michael (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The COVID-19 pandemic has not only created such a massive impact on health but has also drastically transformed the global educational landscape, and with the World Health Organization (WHO) predicting the pandemic to last beyond 2021, Higher Education Institutions across the country resort to various pedagogical methodologies to ensure the continuous delivery of instruction amidst the pandemic, including the use of Open Educational Resources (OER). OER have been widely used in the Marinduque State College since the implementation of remote learning modality in the institution. Given that this is the first semester that these materials have been widely-used in the college, this study sought to determine the perceptions of students on OER being used for their major courses, particularly for English Language Studies (ELS). This mixed method study considered the 2nd year BA-ELS students as participants, and the necessary data was gathered through a Google Forms survey questionnaire. This paper also aimed to determine perceptions of the participants on the learning materials being used for their English Phonology and Morphology course in terms of content, organization & presentation, and accessibility. Results reveal that participants have a general positive perception with OER in terms of content and organization & presentation. However, participants seem to struggle with its accessibility, as the materials are published on platforms that require internet access.